Accurate measurement of sulfhydryls and TCEP-releasable sulfhydryls in the liquid phase of wine that contribute to ‘reductive’ aromas using LC-MS/MS - Marlize Z. Bekker; Maryam Taraji; Vilma Hysenaj; Natoiya Lloyd (Heliyon, 2024)
Volatile sulfur compounds (VSCs) are important aroma and flavour characters in food and beverage products. The identification and quantification of these extremely reactive and volatile compounds pose analytical challenges which demand selective and sensitive methods. In this study, a novel quantification method was developed to analyse sulfhydryls as well as the total pool of sulfhydryls which can be released after tris(2-carboxyethyl)phosphine (TCEP) addition from disulfides, polysulfides, metal-bound and other yet to be identified sources naturally present in wine. The majority of methods for VSC quantification analyse VSCs in wine headspace, whereas this method measures sulfhydryls and TCEP-releasable sulfhydryl species, which likely include free and metal-bound sulfhydryl forms, in the liquid phase of wine using UHPLC-MS/MS. Sulfhydryls were derivatised with N-(2-ferroceneethyl) maleimide (FEM), subsequently, followed by differential labelling of sulfhydryls released after TCEP addition with ferrocenecarboxylic acid-(2-maleimidoyl)ethylamide (FMEA). Analysis of commercial wines revealed the presence of hydrogen sulfide, methanethiol, ethanethiol, and 2-mercaptoethanol at aroma-active concentrations. Significant positive correlations were found between MeSH and CH3–S-R TCEP-releasable species, and significant positive correlations were found between EtSH and CH3–CH2–S-R TCEP-releasable species. This method provides important information on sulfhydryls, and may also provide insights into a wine's risk of developing ‘reductive’ faults post-bottling from latent sources.